First whole genome sequencing of Staphylococcus aureus isolates from Iraq: Insights into zoonotic relations and biofilm-related genes - Mohammed A. Al-Bukhalifa; Hassan M. Al-Tameemi (Open Veterinary Journal)
Background: Staphylococcus aureus is a significant zoonotic pathogen capable of causing infections in both humans and animals. The bacterium's capacity to develop biofilms and resistance to many different antibiotics has raised significant concerns for public health. Furthermore, studies have demonstrated that horizontal gene transfer enables the transfer of deleterious features between strains found in humans and animals, consequently rendering treatment and control efforts more challenging.